Artificial Intelligence in Higher Education: Development Trends and New Reality - CHERVONA, LESYA; LAKUSHA, NATALIIA; KROKHMAL, NATALIIA; MYROSHNYCHENKO, SERHII (Journal of Education, Technology and Computer Science, 2023)
The article reveals various aspects of the use of artificial intelligence (AI) in higher education. Prospects for the use of AI in higher education are discussed, and specific examples of the use of AI for educational purposes are considered. AI, having great potential for improving the quality of higher education, also carries potential risks of use that must be taken into account. The role of artificial intelligence in the educational process of higher education, evaluation and management of educational processes is emphasized. That is why attention is focused on the issue of what aspects are behind the use of AI in education. The issue of ethical and social consequences of the use of AI in education is discussed.